The uses of smart phones and their sociopolitical implications on Egyptian society - EL Sayed, Yousra Mohsen (AUC Knowledge Fountain, 2015)
Socio-political awareness of a nation is the cornerstone for building well informed citizens that are the heart of any societal development and progress. This study examined the various uses of smart phones mobiles and their sociopolitical implications on the Egyptian Society from the January 25th revolution to the present. The research explores the impact of the mobile smart phones’ usage on changing the reality of the Egyptian society. The primary research linked the uses and gratification theory and the Apparategeist theory to the Egyptians’ civic engagement attitudes and political participation in the real world. Findings of the study show that accessing and acquiring knowledge through mobile smart phones is the main use of smart phones mobiles by Egyptian media experts and youths during the January 25th revolution, followed by June 30th and up-to-date. Based on the results of this study, smart phones’ usage for “surveillance” and being a source of information and dissemination of news is the main pillar for creating a well-informed Egyptian citizen who can transform the social and political face of the Egyptian society. The testimonies also show that the most used news websites by respondents are Youm 7, CNN, BBC and AL Arabyia. By being civically and politically engaged through smart phones’ usage, Egyptians are becoming active key players in sustaining and nourishing the democratic process. The findings also illustrated other uses of smart phones, however not as significant as being a source of accessing and acquiring news. The study uses a quantitative survey methodology in exploring the uses of smart phones and their sociopolitical implications before and after the revolution. It also observes the relationship between the usage and being civically and politically engaged in real life behaviors and or attitudes. Two primary surveys were conducted among two different samples. The first was a purposive sample of Egyptian elite media experts ( 50 participants) whom are civically engaged and actively involved in the Egyptian revolution phase and the second was a stratified sample of elite university students ( 200 participants). The research employed the two questionnaires to examine the relationship between smart phones’ usage and civic engagement attitudes of Egyptians in real life. The study proceeded with conducting a comparison between Egyptian media experts’ perspective of smart phones’ usage and the revolution and that of the Egyptian youths